Adverse health effects related to mercury exposure from dental amalgam fillings: toxicological or psychological causes? - Bailer, Josef; Rist, Fred; Rudolf, A.; Staehle, Hans Jörg; Eickholz, Peter; Triebig, Gerhard; Bader, Michael; Pfeifer, U. (Psychological medicine, 2001)
Possible adverse health effects due to mercury released by amalgam fillings have been - discussed in several studies of patients who attribute various symptoms to the effects of amalgam - fillings. No systematic relation of specific symptoms to increased mercury levels could be established - in any of these studies. Thus, a psychosomatic aetiology of the complaints should be considered and - psychological factors contributing to their aetiology should be identified.